Perspective: Opportunities and Scope for Expanded Deworming Programs for Soil-Transmitted Helminths in India - Aruldas, Kumudha; Khera, Ajay Kumar; Ajjampur, Sitara Swarna Rao (Frontiers in Tropical Diseases, 2021)
The current deworming strategy for soil-transmitted helminthiases (STH) is focused on pre-school and school aged children and women in the reproductive age to eliminate morbidity. Studies indicate that treating the entire population would probably be a better elimination strategy by reducing re-infections. In India, in addition to testing the effectiveness of community-wide mass drug administration to eliminate STH, it is crucial to consolidate deworming activities included in various ongoing programs like lymphatic filariasis and anemia control where adults also access treatment. Understanding the gaps in deworming will help plan policy changes and program strategies for STH elimination.